Heterogeneous SRAM Cell Sizing for Low-Power H.264 Applications - Kwon, Jinmo; Chang, Ik Joon; Lee, Insoo; Park, Heemin; Park, Jongsun (IEEE transactions on circuits and systems. I, Regular papers, 2012)
In low-voltage operation, static random-access memory (SRAM) bit-cells suffer from large failure probabilities with technology scaling. With the increasing failures, conventional SRAM memory is still designed without considering the importance differences found among the data stored in the SRAM bit-cells. This paper presents a heterogeneous SRAM sizing approach for the embedded memory of H.264 video processor, where the more important higher order data bits are stored in the relatively larger SRAM bit-cells and the less important bits are stored in the smaller ones. As a result, the failure probabilities significantly decrease for the SRAM cells storing the more important bits, which allows us to obtain the better video quality even in lower voltage operation. In order to find the SRAM bit-cell sizes that achieve the best video quality under SRAM area constraint, we propose a heterogeneous SRAM sizing algorithm based on a dynamic programming. Compared to the brute-force search, the proposed algorithm greatly reduces the computation time needed to select the SRAM bit-cell sizes of 8 bit pixel. Experimental results show that under iso-area condition, the heterogeneous SRAM array achieves significant PSNR improvements (average 4.49 dB at 900-mV operation) compared to the conventional one with identical cell sizing.